PENGARUH AGENCY COST TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Anshori, M.Taufiq (Universitas muhammadiyah palembang, 2015)
Formulation of the problem in this study is how the influence of cost agency without control variables and with control variables to dividend policy on the companies listed in the Jakarta Islamic Index, and how the Islamic perspective on the agency problems and dividend policy. This study isdesigned as associative and descriptive. Population in this studies are the companies entering more than 5 times during the period of 2010-2014, there were 23 companies as the sample. This study use simple random samplingby using lottery technique in determining the sample. The data used are secondary data from financial statements company. Model analysis used is multiple linear regression analysis, and for hypothesis analysis by using F and t test with significance level of 5%. Research results simultaneously (F test) showed negative significant effect on dividend policy agency cost without the control variables as well as after the added control variables. t test results showed insider ownership (X1) significant negative effect on the dividend policy (Y) either without or after the with control variables, whereas institutional ownership (X2) significant positive effect on dividend policy (Y) either without or after the controlvariables.